2011
DOI: 10.5194/acp-11-2083-2011
|View full text |Cite
|
Sign up to set email alerts
|

New cloud chamber experiments on the heterogeneous ice nucleation ability of oxalic acid in the immersion mode

Abstract: Abstract. The heterogeneous ice nucleation ability of oxalic acid in the immersion mode has been investigated by controlled expansion cooling runs with airborne, ternary solution droplets composed of, (i), sodium chloride, oxalic acid, and water (NaCl/OA/H 2 O) and, (ii), sulphuric acid, oxalic acid, and water (H 2 SO 4 /OA/H 2 O). Polydisperse aerosol populations with median diameters ranging from 0.5-0.7 µm and varying solute concentrations were prepared. The expansion experiments were conducted in the AIDA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 48 publications
6
59
0
Order By: Relevance
“…Wagner et al observed a similar effect in crystallization of ternary solution droplets composed of oxalic acid, NaCl, and water in the AIDA cloud chamber at 244 K. 69 There, the crystallization of NaCl dihydrate was facilitated by the presence of oxalic acid crystals. Recently, the CaSO 4 was identified by means of EDX analysis of the sea salt particles collected in the field.…”
Section: G Temperature-dependent Formation Of Nacl Dihydrate In Ssa mentioning
confidence: 77%
“…Wagner et al observed a similar effect in crystallization of ternary solution droplets composed of oxalic acid, NaCl, and water in the AIDA cloud chamber at 244 K. 69 There, the crystallization of NaCl dihydrate was facilitated by the presence of oxalic acid crystals. Recently, the CaSO 4 was identified by means of EDX analysis of the sea salt particles collected in the field.…”
Section: G Temperature-dependent Formation Of Nacl Dihydrate In Ssa mentioning
confidence: 77%
“…A detailed description of the chamber preparation, the chamber instrumentation, and the expansion cooling technique for ice cloud studies is given in the recent papers by Wagner et al (2010Wagner et al ( , 2011. In the following, we therefore only give a brief introduction to the chamber and its intrumentation.…”
Section: The Cloud Simulation Chamber Aidamentioning
confidence: 99%
“…To determine the purity of our sample, and to compare this with previous observations, the dust mineralogy of a bulk illite NX sample was characterized using XRD (Waseda et al, 2011) prior to distribution. In addition, complementary energy dispersive X-ray (EDX) spectroscopy analysis was performed to characterize the elemental composition of in-dividual particles.…”
Section: Illite Nx Characterizationmentioning
confidence: 99%
“…The same disperser type was used at both chambers for particle generation, and the upstream cyclone impactors (D 50 ∼ 1 and 2.5 µm) were similarly deployed to filter out any larger particles and safeguard against injecting these particles into the vessel. We note that a linear correction factor of ∼ 2 was applied to convert the optical diameter measured by the welas-OPC to the APS-inferred volume equivalent di-ameter in several studies (Wagner et al, 2011;Hiranuma et al, 2014a).…”
Section: Particle Size Distributionmentioning
confidence: 99%